Letter to the editor, Alphabetical index, Contents - Journal , Lithuanian Mathematical (Lithuanian Mathematical Journal, 1965)
Original title in Russian and Lithuanian:Письмо в редакцию, Алфавитный указатель, СОДЕРЖАНИЕLaiškas redakcijai, Alfabetinė rodyklė, TURINYS